Character Education of Local Wisdom-Based: A Study of Moral Aspect of Quotes Belong to Bugis People - Ilham, Muh.; Rahman, Fathu (Journal of Ecohumanism, 2024)
Research on character education is an important aspect in forming individual qualities, especially amidst the complex challenges that arise in this digital era. In this context, actualizing the value of character education based on local wisdom offers relevant and holistic solutions in dealing with current strategic issues. This research explores the importance of integrating local values into character education as an option to strengthen cultural identity, improve social and moral skills, and face complex social challenges in the digital era. The aim of this research is formulated as follows; 1) to explore the value of local wisdom that grows in society and has been passed down from generation to generation, and 2) to actualize the moral messages contained in the character teachings of indigenous communities which are very likely to contribute to character education. The qualitative descriptive research method was applied to achieve the research objectives. Data was collected through interviews, reading documents and reinterpreting the meaning behind quotes for character education. The results of the research show that there is potential for the oral quotes of pappaseng of Bugis to be a way of strengthening character education that is not understood by the millennial generation. They don't care because they think oral quotes are just false expressions that are no longer relevant to today's needs. The implications of this research raise new awareness among millennials in particular that they have a cultural heritage that is very important to preserve.